STUDY ON COMMUNITY RESILIENCY DEALING WITH NATURAL DISASTER PREPAREDNESS IN PANDANSARI KRAJAN VILLAGE, PONCOKUSUMO SUB-DISTRICT, MALANG REGENCY - Debora, Oda; Syukkur, Achmad (Journal Nursing Care and Biomolecular, 2018)
Introduction: Natural disasters are phenomenon that were noticed throughout the world and Indonesia because itâs great impact to the worldâs economic. Villagers of Pandansari Krajan had experienced many natural disaster phenomenon, but they had less participation in disaster risk reduction activities. The aimed of this research was to evaluate which factor was the most well-prepared for community resilience strengthening program. Method: This research was a non-experimental, descriptive survey method was used. The population was the entire adult at Pandansari Krajan village, with the number of respondents as many as 363, taken with simple random sampling technique. Result and Analysis: The result showed that the respondents knowledge on the disaster risk in his place was the best score, that was 18.88. The lowest average score was the implementation of disaster risk reduction activities, that was 26.71 from the maximum score of 64. Disaster theory had been given and many natural disasters events were experienced by the villagers, those were the main reasons for this high score. However, resource-based economy strengthening played an important role along with the process of increasing community resilience. In addition to the economic condition, communication between communities and government need to be improved so that disaster risk reduction programs can be aligned between the two parties. Discussion: Training activities were needed to strengthen the communitys economy so that resiliency can be improved. In addition, further research is needed to look forward for the most vulnerable groups when disaster arrive.